Asupan mikronutrien sebagai faktor risiko kejadian sindrom pramenstruasi pada wanita vegetarian - Renata, Maria Dolorosa Sus; Widyastuti, Nurmasari; Nissa, Choirun (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background : Inadequate of vitamin B6, magnesium, zinc, and calcium intake and a lower body mass index can lead to Premenstrual syndrome (PMS) in vegetarian woman. The objective of this study was to determine the association between micronutrients intake, nutritional status and PMS among vegetarian women.Objectives : The objective of this study was to determine the association between micronutrients intake, nutritional status and PMS among vegetarian women.Methods : A cross sectional study was conducted to 44 vegetarians women.Subjects of this study were collected consecutively. Dietary intake were measured by Semi Quantitative Food Frequency Questionnaire (SQFFQ). Score of PMS were measured by Shortened Premenstrual Assessment Form (sPAF).Physical activity were measured by International Physical Activity Questionnaire (IPAQ). Score of stress level were measured by International Physical Activity Questionnaire (PSS-10). Data were analyzed by Chi Square test and ratio prevalence to determine the risk factor.Results : There were 54.55% of subject have a moderate PMS level. There were a correlation between vitamin B6 and PMS (p=0.019;RP=2.96;95%CI=0.9-10), magnesium and PMS (p=0.033;RP=3.8;95%CI=0.6-23), zinc and PMS (p=0.002;RP=6.17;95%CI=0.9-39), physical activity and PMS (p=0.033;RP=3.79;95%CI=0.6-23), stress level and PMS(p=0.045;RP=0.39;95%CI=0.1-1.3). There were no correlation between calcium intake and PMS (p=0.211;RP=1.816;95%;CI=0.569-5.794), BMI and PMS (p=0.355;RP=0.753;95 %; CI=1.443).Conclusion : Intake of vitamin B6, magnesium and zinc, physical activity and stress level were correlated to PMS. Calcium intake and BMI were not correlated to PMS.